Determinan Minat Penggunaan QRISN( Quick Response Indonesia Standard) pada Nasabah Bank Pembangunan Daerah Bali Cabang Utama Denpasar - Kristina, Ida Ayu Komang; Purnamawati, I Gusti Ayu (Jurnal Akuntansi Profesi, 2024)
AbstractThis research was conducted to find out the influence of Ease Perception, Benefit Perception, Risk Perception, Cost and Security on QRIS Usage Interest in Customers of Bali Regional Development Bank Denpasar Main Branch. The research design used is a quantitative research design using associative methods, using data obtained from questionnaires and measured using the likert scale. The population used in this study is a customer of Bank Pembangunan Daerah Bali Main Branch of Denpasar who uses QRIS. Sampling techniques use incidental sampling. In this study used as a sample is a customer of Bank Pembangunan Daerah Bali Main Branch Denpasar who uses QRIS with a total of 100 respondents. The method used in analyzing data is multiple linear regression analysis using SPSS. 24 for windows. The results of this study showed that the perception of ease, perception of benefits, costs and security had a significant positive impact on the interest in the use of QRIS in customers of the Bali Regional Development Bank's Denpasar Main Branch. While the perception of risk has a significant negative effect on the interest in the use of QRIS in customers of The Bali Regional Development Bank's Denpasar Main Branch.Keywords: Ease Perception, Benefit Perception, Risk Perception, Cost, Security, and Interest in QRIS Use.